2015
DOI: 10.1186/s13075-015-0815-y
|View full text |Cite
|
Sign up to set email alerts
|

Different responses to treatment across classified diseases and severities in Japanese patients with microscopic polyangiitis and granulomatosis with polyangiitis: a nationwide prospective inception cohort study

Abstract: IntroductionThis study aims to elucidate the prognosis and the effectiveness of current treatments for Japanese patients with microscopic polyangiitis (MPA) and granulomatosis with polyangiitis (GPA).MethodsPatients with newly diagnosed MPA and GPA were enrolled in a nationwide, prospective, inception cohort study from 22 tertiary Japanese institutions, and treatment patterns and responses were evaluated for 24 months. Primary outcome measures were rates of remission (Birmingham Vasculitis Activity Score, 0) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 30 publications
2
28
1
3
Order By: Relevance
“…As for clinical course, we elucidated that most Japanese patients with MPA and GPA received treatment with high-dose glucocorticoid and limited-dose cyclophosphamide (CY), and showed high remission and relapse-free survival rates. However, remission with prednisolone at <10 mg/day was observed only in 40% of the patients with remission at 6 months [8,9]. To further analyze the The extent and pattern of organ involvement were quite different between patients with AAV, and the European League Against Rheumatism (EULAR) recommends that patients with vasculitis should be categorized into clearly defined disease states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for clinical course, we elucidated that most Japanese patients with MPA and GPA received treatment with high-dose glucocorticoid and limited-dose cyclophosphamide (CY), and showed high remission and relapse-free survival rates. However, remission with prednisolone at <10 mg/day was observed only in 40% of the patients with remission at 6 months [8,9]. To further analyze the The extent and pattern of organ involvement were quite different between patients with AAV, and the European League Against Rheumatism (EULAR) recommends that patients with vasculitis should be categorized into clearly defined disease states.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the European Vasculitis Study Group (EUVAS)-defined disease severity, Five-Factor Score (FFS), and RPGN clinical grading system could be used for this purpose [10][11][12]. The RemIT-JAV study revealed that the EUVAS-defined disease severity, especially the severe form, was useful for predicting poor renal and vital prognoses [9].…”
Section: Introductionmentioning
confidence: 99%
“…4 . A forma localizada manifesta-se primariamente com envolvimento de ouvido, nariz e garganta, é limitada ao trato respiratório superior e inferior sem envolvimento sistêmico ou sintomas constitucionais 1,4,11,20 . A forma sistêmica inicial pode acometer qualquer órgão ou sistema, sem conferir risco de dano irreversível a órgãos ou risco de morte.…”
Section: Diagnósticounclassified
“…Recomenda-se a combinação de corticosteroides sistêmicos com outras drogas imunossupressoras 20,21 . Nesse caso, prednisona ou prednisolona 0,5 a 1mg/kg/ dia (dose máxima de 80mg/dia) pode ser utilizada por 1 a 4 semanas.…”
Section: Corticoidesunclassified
“…A nationwide prospective inception cohort study in Japan revealed that AAV classification, the type of organs involved, the age of onset, and the treatment patterns were different from those in Western countries (2, 3). …”
Section: Introductionmentioning
confidence: 99%